INTERPERSONAL COMMUNICATION AND MCDONALDIZATION ON ONLINE SERVICE BASED PLATFORM: A STUDY OF GO-JEK USERS AND DRIVERS IN CENTRAL JAVA - Saptono Joko Sulistya (KHIDMAT SOSIAL: Journal of Social Work and Social Services, 2020)
The presence of start-up companies in Indonesia caused many shifts in terms of human interaction. Go-jek, is one of the most influential, whom the applications being downloaded more than 155 million times with 100 million transactions and managed to cooperate with more than 2 million driver partners on early 2019. Go-jek became one of the startup companies that brought many changes in lifestyle, since every transaction can be done through the application. This kind of online services makes Go-jek as the technology products that utilize human services and tends to minimize communication between person to person. It relates to the McDonaldization concept promoted by George Ritzer regarding human work that is being replaced by machines, as well as the loss of communication between people due to the principles of predictability, calculability, efficiency, and control. This study aims to describe the process of interpersonal communication between users and Go-Jek drivers in Central Java using McDonalization theory from George Ritzer. This research used qualitative approach with interview as data collecting method. There were 6 informants interviewed in this study, 3 Go-Jek customers and 3 people from Go-Jek drivers who provide services on a daily basis. The results of this study are communication carried out between the customers and Go-jek drivers as the service provider still occurs. Through those interpersonal communications, they keep optimizing services and minimizing errors, although the four principles of McDonaldization have been applied. Small talks and light conversation also needed when it comes to human service. This also happens because Indonesian used to be friendly and open to have conversations with others in society. Then, the principle of predictability, calculability, efficiency, and control does not really affect interpersonal communication of Go-Jek customers and drivers in Central Java.Keywords: McDonaldization, Go-Jek, communication process, human service